Diagnostic Challenge of Phenotypic Variability in COL2A1-related Disorders: Four Novel Variants That Expand the Clinical Spectrum - Burcu Yeter; Yasemin Kendir Demirkol; Metin Eser; Ahmet Hamdi Akgülle; Betül Sözeri; Heves Kırmızıbekmez (JCRPE)
Objective: Heterozygous COL2A1 gene mutations are associated with type 2 collagenopathies, characterized by a wide, diverse, and overlapping clinical spectrum in related diseases. Our goal is to describe the clinical, radiological, and molecular findings of patients with COL2A1-related dysplasia and investigate the phenotype-genotype correlation. We also highlight the challenge of categorizing COL2A1-related diseases with similar clinical and radiological phenotypes. Methods: Six patients from five unrelated families presented with disproportionate short stature.delayed motor milestones, waddling gait, normal intelligence, and similar radiological features, including delayed epiphyseal ossification, epimetaphyseal changes, scoliosis, lordosis, and platyspondyly. All underwent whole exome sequencing. Demographic, clinical, laboratory, and radiological data were retrospectively obtained from hospital records. Segregation analysis was conducted using Sanger sequencing in all patients. Results: Based on clinical, radiological, and molecular results, the six patients were categorized into kniest dysplasia, spondyloepiphyseal dysplasia congenita, and spondyloepimetaphyseal dysplasia Strudwick type. Four novel variants (c.1023+2T>C, p.Gly465Asp, p.Gly855Asp, p.Gly669Ala) were identified in the COL2A1 gene. Conclusion: Accurate classification of type 2 collagenopathies is vital to provide appropriate genetic counseling. Predicting extraskeletal manifestations and reducing morbidity through early diagnosis and treatment will significantly improve the quality of life for patients.